Food across borders - García, Matt; DuPuis, E. Melanie (Erna Melanie), 1957-; Mitchell, Don, 1961- (Rutgers University Press, 2017)
The act of eating defines and redefines borders. The stories told in Food Across Borders highlight the contiguity between the intimate decisions we make as individuals concerning what we eat and the social and geopolitical processes we enact to secure nourishment, territory, and belonging.